Process analysis of spray atomization of dissolved polymers for manufacturing of blood-compatible textile implants. (November 2018) - Nadzeyka, Ingo; Bolle, Eleonore; Moos, Martin; Kunitz, Paula; Steinseifer, Ulrich; Schmitz-Rode, Thomas
The use of porous polymer materials for vascular prostheses demonstrates promising results. Fleece-like non-woven structures can be generated by atomization of dissolved polycarbonate urethanes. This article focuses on the manufacturing process for the fleece structures. The solution is atomized through a high-volume low-pressure nozzle. The solvent evaporates during time of flight to target, so that small fibres are formed from each drop of solution. By using different rotating molds and positioning systems, tubular shapes or open surfaces can be generated. The manufacturing process is described in detail. The usability of different grades of polycarbonate urethane is tested and the time necessary for evaporation of the solvent from the mesh is assessed. The influence of several basic parameters on the mechanical properties of the generated non-woven material is analysed and discussed.